Analysis of temperature projections in the Koshi River Basin, Nepal. (17th April 2015) - Agarwal, Anshul; Babel, Mukand S.; Maskey, Shreedhar; Shrestha, Sangam; Kawasaki, Akiyuki; Tripathi, Nitin K.
ABSTRACT: This study analyzes temperature projections in the Koshi River Basin in Nepal using data obtained from ten General Circulation Models (GCMs) for three IPCC Special Range of Emission Scenarios (SRES): B1, A1B and A2. Low resolution data of minimum and maximum temperature obtained from the selected GCMs was downscaled using the statistical downscaling model Long Ashton Research Station Weather Generator (LARS‐WG) for ten stations located in two physiographic regions of the study area: the Middle Mountains (1500–2700 m) and the Siwalik Hills (700–1500 m). The projected temperature and differences in projections among individual GCM projections for changes in the mean value of seasonal and annual T min and T max are presented for three future periods: 2011–2030 (2020s), 2046–2065 (2055s) and 2080–2099 (2090s). We also analyzed the baseline period and future T min and T max data through seven indices, as recommended by the Expert Team on Climate Change Detection, Monitoring and Indices (ETCCDMI). Results show that the LARS‐WG model performs well when downscaling T min and T max . An increase in seasonal as well as mean annual minimum and maximum temperature is projected for all three future periods. Projected warming, as well as the differences among projections from different GCMs, increases with time for each of the three scenarios. The cold years during the 2055s and 2090s are expected to be hotter than the hot years during the baseline period. The increase in temperature, as well as the range of uncertainty, is expected to be higher in the Mountains than in the Hills. The number of summer days and tropical nights is expected to increase during all three future periods. The temperature of the coldest day, coldest night, warmest day and warmest night is also expected to increase in both the regions during all three future periods.